A verticalização do ensino no eixo de recursos naturais do IFSP - campus Barretos: potencialidades e resistências - Souza, Ivan Pollarini Marques de (Universidade Federal de São Carlos, 2025)
Verticalisation and integration are fundamental assumptions of the education offered by Federal Institutes. However, the concept of verticalisation, as well as its organisation and potential in education, is not well defined. Thus, through this research, based on the contributions of polytechnic training and the school of work, developed by Soviet thinkers and Gramsci, we sought to define the conceptual understandings of verticalisation contained in internal documents related to the technological axis of Natural Resources at IFSP-Campus Barretos, as well as in internal documents related to the Campus itself and IFSP. To this end, the concepts contained in the specific literature on the subject were defined in order to present possible clarifications in the different understandings of the concept. Furthermore, contributed directly to the development of a broad concept of verticalisation, which presents it as linked to the fundamentals of omnilateral, integral and polytechnic training of workers, as well as understanding its organisation in the pedagogical and administrative-managerial dimensions, and assumes the possibility of the occurrence of verticalised training both externally and internally to the institution, in the search for the formation of a new ruling class. Based on these concepts, and on the contribution to the conceptual development itself, the institutional documents were analysed from the perspective of Historical-Dialectical Materialism, based on the analysis of the context. The selection of documents took place both internally and externally to the Campus, where internal documents were selected between 2010 and 2023, beginning with the founding of the IFSP-Campus Barretos. Specifically, for documents internal to the technological axis of training in Natural Resources, documents issued between 2017 and 2023 were selected, since this period included the opening of higher education in Agronomy, which guaranteed the basic condition for the verticalisation of the axis studied and culminated at the end of the 2019-2023 Institutional Development Plan period. Through analysis, a narrow understanding of verticalisation was evident in the internal documents of the Campus and the Axis. At the same time, the deterioration of the concepts of integration and verticalisation in the documents over time was demonstrated. Furthermore, it was demonstrated that conceptual deterioration occurs at an accelerated rate in documents prepared by the rector's office from 2022 onwards, transforming verticalisation into a synonym for simplified training, based on the use of knowledge obtained in technical courses at secondary level as equivalent to higher education knowledge. Internally within the axis, although the conception of verticalisation contained in the documents is narrow, the occurrence of verticalisation in the Natural Resources axis is evident, with internal and external training courses taking place on campus. In addition, actions linked to the pedagogical dimension that could potentially promote internal verticalisation within the axis studied were identified and characterised. It is hoped that this research will enrich the debate on verticalisation, its potential and its impact on the training of the working class, preferably that linked to the precepts of polytechnic training.
The verticalization of teaching in the natural resources axis of the IFSP - Barretos campus: potentialities and resistances
Keywords: Verticalização do Ensino; Integração do Ensino; Formação Integral; Dualidade do Ensino; Formação Omnilateral; Verticalisation of Education; Integration of Education; Comprehensive Education; Duality of Education; Omnilateral Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::ENSINO PROFISSIONALIZANTE; 4. Educação de Qualidade